Nota sobre um depósito de cruzados novos da região de Guimarães - Centeno, Rui (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
We study a set of 190 portuguese silver coins (Cruzados Novos), minted between 1750 and 1836, presumably found in the area of Guimarães at an earlier date to 1951, analyzing its composition and comparing it with a similar hoard discovered in Régua (Vila Real).